Pengaruh Pengetahuan, Religiusitas, Dan Persepsi Kegunaan Terhadap Minat Muzakki Membayar Zakat, Infak, Dan Sedekah Melalui Qris Di Baznas Banyumas - Nur Halisah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The use of QRIS as a digital payment method in Indonesia has shown a positive trend since it started operating in 2020. In 2022, the number of people using QRIS increased by 92.5% from last year to reach 28.75 million. However, the existence of QRIS at BAZNAS Banyumas based on data obtained from BAZNAS Banyumas, muzakki are not yet interested in paying zakat through QRIS, in a year there are only 132 QRIS users, even though the use of QRIS transactions is intended nationally as an increasing transaction method. From an Islamic perspective, a person's interest in paying zakat, infaq, and alms is their desire as muzakki as a form of worship and social in accordance with the word of Allah SWT in QS At-Taubah verse 103. This study aims to analyze the influence of knowledge, religiosity, and perception of usefulness on the interest in paying zakat, infaq, and alms through QRIS at BAZNAS Banyumas. This study uses a quantitative research method. The primary data from this study were obtained using a nonprobability sampling technique with the drawing of research samples using purposive sampling. The population of this study was muzakki BAZNAS Banyumas with a total sample of 300 respondents. The data analysis techniques used in this study were multiple linear regression analysis and t-test, F-test and R2-test. The results of this study indicate that knowledge has a significant influence on the interest of muzakki in paying zakat, infaq, and alms through QRIS, religiosity has an insignificant influence on the interest in paying zakat, infaq, and alms through QRIS, and the perception of usefulness has a significant influence on the interest in paying zakat, infaq, and alms through QRIS. While the simultaneous results show that knowledge, religiosity, and perception of usefulness have an effect on the interest in paying zakat, infaq, and alms through QRIS.